A metodologia de ensino de Marie Curie como uma proposta subjacente para a aprendizagem significativa de conceitos físicos nos anos iniciais do Ensino Fundamental - Cezar, Derli Cleria da Silva (2012)
This present work, made from a theoretical and practical research about the teaching of Physics in the earlier years of the Primary Education at a private school in Cuiabá – MT, focused in the pedagogy of Marie Curie whom, in her own time, preoccupied with the integral formation of the citizen as a thinking creature, acting and co-responsible by the destiny of the society. It’s a research that surely will contribute to the teaching-learning process, once that the learning of Natural Sciences (Physics) bears great prominence on the formation of the citizen, inclusively referring to the alphabetization, that, nowadays, does not only is reduced in skills such as reading and writing, but in a “scientific alphabetization”, which covers all the faces of the alphabetization process. Facing this fact, we propose the using of experimentations in Primary Education, in conformity to the methodology of Marie Curie, making good use of the natural curiosity of the students to work the physics concepts that are present in the daily lives, with the insertion of the scientific language in their cognitive structure. The absence of such language may be one of the existent difficulties in the learning when the scholar is studying the High School, or even the Higher Education. Probably the difficulty on learning Physics have as reasons agents which come to sight in the earlier years, when the concepts of sciences are formally presented. The boarding of the physic themes can to favor the comprehension of the dynamics and the process of teaching in the classroom and in the laboratory. According this way, practical classes have been developed in the laboratory of Physics of the summoned school, with the participation of the 5th year students and their respective professors. Throughout these classes, have been considerated each child’s spontaneous knowledge, acquired in their actual and experiential worlds, together with the teaching-learning process in Physics. Facing the inquietude of the children on the pursuit of answers and logical interpretations in order to solve the proposition presented in each class, a conviction is brought that the practical work with laboratory classes is unquestionable for the obtainment of the expected effects in the teaching of Natural Sciences (Physics) which, consequently, will result on the gradual construction of the knowledge.